2014
DOI: 10.4321/s0004-05922014000400007
|View full text |Cite
|
Sign up to set email alerts
|

Percepção de qualidade da carne bovina com marca no sul do Brasil

Abstract: SUMMARYThe objective of this study was to analyze the quality perceived by different actors in beef marks chain production at Rio Grande do Sul state. The data were obtained through a descriptive exploratory research, using as an instrument of data collection standards a based structured questionnaire with six questions covering seven levels of the beef market chain: i) consumers, ii) butchers, iii) perishable managers and iv) supermarket general managers, v) sales managers of meat and vi) cattle purchase mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
0
1
0
2
Order By: Relevance
“…304 of 1996, of the Ministry of Agriculture, Livestock and Supply (Brasil, 1996), which establishes criteria for meat distribution and marketing activities, aiming at consumer health (Silva Filho et al, 2018). McCarthy et al (2003) and Maysonnave et al (2014) accounted that both attitudes and subjective norms influenced the intention to buy meat, but attitude was the most significant construct. The determinant attributes in the choice were related to health, satisfaction, pleasure in consuming meat, food safety, and, in fewer cases, price and concerns about animal welfare and the environment (McCarthy et al, 2003;Tatum, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…304 of 1996, of the Ministry of Agriculture, Livestock and Supply (Brasil, 1996), which establishes criteria for meat distribution and marketing activities, aiming at consumer health (Silva Filho et al, 2018). McCarthy et al (2003) and Maysonnave et al (2014) accounted that both attitudes and subjective norms influenced the intention to buy meat, but attitude was the most significant construct. The determinant attributes in the choice were related to health, satisfaction, pleasure in consuming meat, food safety, and, in fewer cases, price and concerns about animal welfare and the environment (McCarthy et al, 2003;Tatum, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As part of a balanced diet, meat originating from these systems is healthy and does not affect the lipid profile of consumers (Lobato et al, 2014). In this respect, healthiness and geographic identification are highly considered criteria by consumers that seek product safety (Maysonnave et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…and gaining market share with the introduction of differentiated meat and/or milk products, in terms of intrinsic or organoleptic traits, as well as products with geographical identification (BRANDÃO MAYSONNAVE ET AL., 2014;MORAES ET AL., 2013;VEIGA 2011). In Paraguay, Britez et al (2019 also demonstrated the importance and appreciation of products of naturalized breeds with geographical identification, although the lack of knowledge and marketing is still a factor to be overcome.…”
mentioning
confidence: 99%